Carga viral de SARS-CoV-2 e sobrevida em pacientes com COVID-19 no municipio de São Carlos: estudo de coortes - Pessoa, Nathalia Gardin (Universidade Federal de São Carlos, 2023)
Introduction: There is evidence that high SARS-CoV-2 viral load in respiratory secretions is related to greater disease severity. However, some authors have observed a high virus load in respiratory secretions even in asymptomatic people. Several factors may be implicated as higher inoculum in transmission, poor replication control, lower response to treatment. Thus, systematic studies of influence of viral dynamics in respiratory secretions on COVID-19 lethality are needed. Objective: The main objective of this study is to evaluate the association between the evolution of the viral load of SARS-CoV-2 in respiratory secretions and the prognosis of severe COVID-19, in terms of the need for non-invasive mechanical ventilation (NIMV), invasive mechanical ventilation (IMV), or evolution to death or sequelae, as well as the factors associated with these unfavorable outcomes. Methods: Longitudinal descriptive study of cohorts. Exposure factor: SARS-CoV-19 viral load estimated by the ∆Ct method; outcome: NIMV, IMV, cardiac or pulmonary sequelae, discharge/death. The study included adult individuals (age >=18 years), with a diagnosis of Severe Acute Respiratory Syndrome by SARS-CoV-2 diagnosed by RT-PCR, admitted to the internal medicine ward of HU-UFSCar, and who signed the informed consent. Patients were evaluated using a standardized questionnaire with demographic, epidemiological, clinical, virological, laboratory and imaging information, need for support, and treatment, using the RedCap program. The patients were reevaluated on four more occasions when they were submitted to clinical and laboratory evaluation and new collections of RT-PCR for SARS-CoV-2 in rhino and oropharyngeal secretion (48-72h, 6-8 days, 10-15 days, 20- 25 days). Patients were evaluated for evolution with the need for invasive or non-invasive mechanical ventilation, discharge or hospital death, pulmonary and cardiovascular sequelae, and 120-day survival. Results: Between October 2020 and November 2021, 23 patients with SARS due to SARS-CoV-2 were included in the study. About half of the patients required O2 support with a reservoir mask and 26.1% underwent invasive mechanical ventilation. Two patients evolved to death. The SARS-CoV-2 viral load by the ΔCt method in naso/oropharyngeal swabs remained higher (above 10) after one week of hospitalization in the patients who died. Other factors associated with death were age greater than 60 years and some characteristics at admission: hypothermia, bradycardia, hypotension, electrocardiographic changes (widening of the p-wave and 1-degree AV block), neutrophil counts below 5000 cells/mm3, D-dimer greater than 1mg/L; CRP less than 10 mg/dL; and total bilirubin less than 0.4 mg/dL. The two patients who died did not receive corticosteroids within the first 72 hours of hospitalization. It remains to assess the demographic, epidemiological, clinical, laboratory, imaging and treatment factors associated with the need for non-invasive mechanical ventilation, invasive mechanical ventilation and sequelae. More than 95% of patients evolved with production of neutralizing antibodies after severe COVID-19, with a median inhibition level of 99.3%.
SARS-CoV-2 viral load and survival in patients with COVID-19 in São Carlos city: a cohort study
Keywords: Carga viral; Viral load; SARS-CoV-2; COVID-19; Prognosis; Prognóstico; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA::DOENCAS INFECCIOSAS E PARASITARIAS